Relaciones interpersonales y participación social de las socias del Comité de Vaso de Leche Tumi de Oro, Gran Chimú, El Porvenir, 2021 - Alayo De La Cruz, Katherine Marly (2022)
The present investigation was carried out with the purpose of analyzing the influence of interpersonal relationships on the social participation of the members of the Tumi de Oro Glass of Milk Committee. The sample universe was made up of 45 members of the Vaso de Leche Committee, during the investigation three methods were applied, such as inductive - deductive, analytical - synthetic and statistical; Likewise, techniques such as interview, survey and observation were used, which were presented through instruments such as the interview guide, the interview record, the questionnaire, the observation guide and the observation record, which were applied to the members of the Committee. According to the analysis carried out and the results obtained in the investigation, it is evidente that interpersonal relationships positively influence the social participation of the partners, since 93.33% maintain adequate communication that allows them to express their opinions in a safe, direct and respectful way. their partners, causing 77.78% to actively participate when they are grouped into work teams, on the other hand, 86.67% of the partners consider that their decisions are taken into account, encouraging 80.00% to have the initiative to propose activities in Improvement of the Committee, showing that 100.00% of the members feel committed to the Tumi de Oro Vaso de Leche Committee.